Analysis of Character Education Aspects in Narrative Texts of the Electronic Textbook “Developing English Competencies” (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2013)
The issue of character education has mushroomed recently as many as social problems in Indonesia. Thus, character education should be taken into consideration in teaching and learning activity. The aim of this study is to identify the character education aspects in narrative texts found in the electronic textbook used for senior high school students grade XI entitled Developing English Competencies based on the eighteen character education aspects mandated by the Ministry of National Education. This research applies descriptive qualitative method. In collecting the data, the writer used documentary method. The research instrument used in this study was documentation protocol and check list. The result of this research shows that there are 301 sentences from 605 sentences found in all the narrative texts which contain the character education aspects. So the percentage is 49,75 %. The sentences in the 17 narrative texts are relevant to the eighteen character education aspects.